Do menus provide added value to signposts in print monolingual dictionary entries? An application of Linear Mixed-Effects Modelling in dictionary user research - Ptasznik, Bartosz; Lew, Robert (Oxford University Press, 2014)
There is some evidence that language learners as dictionary users benefit from access to sense-guiding devices. This study is a first attempt at comparing the efficiency (entry consultation time) and effectiveness (accuracy of sense selection) of sense signposts against a combination of signposts and menus in print monolingual dictionaries for learners of English. Experimental data from 118 intermediate Polish students of English were collected, testing sense-guiding devices in noun and verb entries of varying length. A Linear Mixed-effects Model analysis with planned comparisons was carried out on the data. Based on a sample of items larger than in previous studies, this study confirms the benefits of signposts in speeding up access to target senses. However, results indicate that adding menus to signposts does not improve search speed or sense selection accuracy any further.
Keywords: dictionaries; entry navigation; data access; access facilitators; English; linear mixed-effects model